Combined Application of a Novel Robotic System and Exoscope for Microsurgical Anastomoses: Preclinical Performance - Wessel, Kai J.; Wendenburg, Isa; Gorji, Shaghayegh; Dermietzel, Alexander; Aitzetmueller, Matthias M.; Varnava, Charalampos; Wiebringhaus, Philipp; Klietz, Marie-Luise; Hirsch, Tobias; Kueckelhaus, Maximilian (Journal of Reconstructive Microsurgery Open, 2023)
Background The concept of robotic microsurgery is becoming increasingly known as several robotic systems tailored to the specific needs of microsurgery are being introduced. Training with these devices is essential to draw conclusions about their potential clinical utility. This study describes the training and learning curve of experienced microsurgeons and complete novices using such a robotic surgical system in combination with an exoscope.Methods Four experienced microsurgeons and three complete novices performed a total of 62 manual and robot-assisted anastomoses. The time for anastomosis completion and surgeon's satisfaction with the anastomosis and with the robotic system were recorded. The anastomoses' quality was assessed using the Structured Assessment of Microsurgery Skills (SAMS) and the Anastomosis Lapse Index (ALI). The Rapid Entire Body Assessment (REBA) was used for ergonomics evaluation.Results All expert microsurgeons and novices improved their performance during training. The average anastomosis time decreased significantly, while satisfaction with the anastomosis and robotic system increased significantly over time. Multiple SAMS score parameters increased significantly throughout robotic but not manual training and the ALI score demonstrated more errors in the manual group. The REBA score displayed a significantly lower risk for musculoskeletal disorders in the robotic group.Conclusion Currently, the first clinical applications of robotic surgical systems specifically designed for microsurgery are being reported. The introduction of such systems into clinical practice can be expected to have a steep learning curve, as demonstrated in our study. Meanwhile, robotic systems for microsurgical procedures may hold great potential for improvement of surgical quality and ergonomics.
Keywords: robotics; microsurgery; anastomosis; learning curve; ergonomics